Highly Enhanced Luminescence Performance of LEDs via Controllable Layer‐Structured 3D Photonic Crystals and Photonic Crystal Beads. Issue 7 (17th May 2018) - Tian, Yu; Chen, Min; Zhang, Jing; Tong, Yu‐Long; Wang, Cai‐Feng; Wiederrecht, Gary P.; Chen, Su
Abstract: Controllable layer‐structured 3D photonic crystals (PCs) are prepared using the combination of the Langmuir–Blodgett (LB) technique and layer‐by‐layer stacking method. They are used for research into the influence of the number of the layers on the enhancement of the efficiency of light emission from light‐emitting diodes (LEDs) and quantum dots (QDs). The luminescence properties of blue, green, and white LEDs are improved dramatically while applying such controllable layer‐structured 3D PCs as reflectors and the enhancement efficiencies are shown to increase with PC thickness. In addition, the fluorescence intensity increases 7.8‐fold and 5.4‐fold for red and green QDs, respectively, and the fluorescence intensity can be accurately controlled by using PCs with different layers. In addition, PC beads with yellow and red photonic bandgaps are used to improve the luminescence of a white LED with angle‐independent enhancement. These beads are simply doped into the phosphor without any other treatment. Interestingly, the light intensity of the PC bead based LED is remarkably enhanced. These quantized enhanced effect of light intensity on the thickness of PC layers, along with new generation of PC bead based LED, might offer a strategy for designing high brightness LEDs with energy‐saving performance. Abstract : A strategy to enhance light efficiency of light‐emitting diodes via controllable layer‐structured 3D photonic crystals angle‐independent photonic crystal beads is demonstrated.